Sketch filter for feature extraction and rendering applications. Issue 13 (1st June 2013) - Kim, G.; Kim, T.; Lim, D.‐H.; Yim, C.
Abstract : First a novel sketch filter based on the maximum filter is proposed. The proposed sketch filter implicitly calculates the complexity of local area, and results in an image which expresses edges and textures as an artist draws a sketch with a pencil. It is then proposed to apply the sketch filter for edge feature extraction, colour pencil drawing, and the animation filtered image. The proposed algorithms work automatically without any interaction and demonstrate impressive results for rendering applications, while requiring a much smaller amount of computations compared to existing schemes.